2010
DOI: 10.1007/s00595-009-4179-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of neuroendocrine differentiation in Japanese breast cancer patients

Abstract: Neuroendocrine differentiation was identified in a subset (26%) of Japanese breast cancer patients, but this appeared to have no relationship with established prognostic factors or patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Although Sapino [7] suggested that ER was highly correlated with long overall survival, our data reveal no specific information on whether ER expression is correlated with prognosis of NEC. Yao [32] and Bofin [9] revealed neuroendorine differentiation in breast carcinoma to be associated with a higher grade of differentiation and a lower malignancy grade, whereas some other studies [33,8,34] suggested that NE markers had no prognostic significance. In this paper, we demonstrate that NE differentiation is not statistically significant in predicting prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although Sapino [7] suggested that ER was highly correlated with long overall survival, our data reveal no specific information on whether ER expression is correlated with prognosis of NEC. Yao [32] and Bofin [9] revealed neuroendorine differentiation in breast carcinoma to be associated with a higher grade of differentiation and a lower malignancy grade, whereas some other studies [33,8,34] suggested that NE markers had no prognostic significance. In this paper, we demonstrate that NE differentiation is not statistically significant in predicting prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a prognostic indicator, an immunostaining profile suggestive of neuroendocrine differentiation in breast cancer has been shown to have limited utility to enhance patient diagnosis or predict outcome [29-32]. However, there is evidence to suggest that ENO2 is altered in breast cancer even though its expression may not have independent prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of neuroendocrine differentiation in breast tumours has been investigated and deliberated for decades, with little consensus being reached on the significance of its presence. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] Part of this uncertainty is probably related to differing definitions of what constitutes neuroendocrine differentiation, leading to inconsistencies in classification of this group of Figure 5. Solid papillary carcinoma (invasive).…”
Section: Carcinomas With Neuroendocrine Differentiationmentioning
confidence: 99%
“…44 With the advent of immunohistochemistry, reactivity of tumour cells for neuroendocrine markers such as synaptophysin and chromogranin has served as light microscopic evidence of neuroendocrine differentiation. 26,29,[32][33][34][35]45 A recent study demonstrated that a subset of breast cancers that lacked immunohistochemical expression of neuroendocrine markers showed upregulation of neuroendocrine-related genes, but the significance of this observation is not clear. 46 Among all invasive breast cancers, neuroendocrine differentiation has been reported in 4-30% of cases, 1,15,26,35,46 on the basis of immunohistochemistry.…”
Section: Carcinomas With Neuroendocrine Differentiationmentioning
confidence: 99%